STUDI EKSPERIMEN PENGARUH KECEPATAN PUTAR MESIN PENGGERAK KOMPRESOR PADA SISTEM KELISTRIKAN AC MOBIL - Esparuling, Esparuling; Sudia, Budiman; Hasanuddin, La (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
The cooling process is essentially a process of transfer of heat energy contained in a room. This study aimsto determine the effect of the rotating speed of the compressor driving machine on the optimum cabinoptimum time temperature in the tropics. Equipment used in this research is panel of electrical system of airconditioner. The research method is done by way of experiment directly on the tool with the speedparameters of the engine speed of the compressor with the temperature to be achieved 20 oC, 22 oC, 24 oCdan 26 oC. The results showed that the higher the compressor turn speed the shorter the time required to coolthe cabin. At the engine speed of 1500 rpm, Cp = 293.07 J/mol.K, W = 0.02542 m, top = 0.00219 hours. At2000 rpm engine speed, Cp = 234.48 J/mol.K, W = 0.0285 m, top = 0.00220 hours. At the engine speed of2500 rpm, Cp = 175.88 J/mol.K, W = 0.03303m, top = 0.00222 hours. At 3000 rpm engine speed, Cp =117.275 J/mol.K, W = 0.04059 m, top = 0.00223 hours. At the speed of 3000 rpm compressor engine speedobtained the actual time of the shortest tact = 2.073 minutes and the optimum time top = 0.00223 hours.Keywords: Compressor, temperature, time, AC panel, and propulsion.